In Silico Inhibitability of Copper Carbenes and Silylenes against Rhizoctonia solani and Magnaporthe oryzae - Nguyen Thi Thanh Hai; Thanh Q. Bui; Tran Thi Ai My; Huynh Thi Phuong Loan; Tran Thai Hoa; Phan Tu Quy; Nguyen Thi Thu Thuy; Dang Thanh Nhan; Nguyen Thi Ai Nhung (Journal of Chemistry)
Copper lighter tetrylenes are promising for inhibition towards Rhizoctonia solani-based protein PDB-4G9M and Magnaporthe oryzae-based PDB-6JBR in rice. Quantum properties of four hypothetic copper complexes of carbenes and silylenes (Cu-NHC1, Cu-NHC2, Cu-NHSi1, and Cu-NHSi2) were examined using the density functional theory. Their inhibitability towards the targeted proteins was evaluated using molecular docking simulation. Quantum analysis predicts the stability of the investigated complexes and thus their practical existability and practicable synthesisability. Their electronic configurations are justified as highly conducive to intermolecular interaction. Regarding ligand-protein as carbenes/silylenes-4G9M inhibitory structures, the stability is estimated in the order [Cu-NHC2]-4G9M (DS −12.9 kcal⋅mol−1) > [Cu-NHSi1]-4G9M (DS −11.8 kcal⋅mol−1) = [Cu-NHSi2]-4G9M (DS −11.7 kcal⋅mol−1) > [Cu-NHC1]-4G9M (DS –11.4 kcal⋅mol−1). In contrast, the corresponding order for the carbenes/silylenes-6JBR systems is [Cu-NHSi2]-6JBR (DS –13.4 kcal⋅mol−1) > [Cu-NHC2]-6JBR (DS −13.0 kcal⋅mol−1) = [Cu-NHSi1]-6JBR (DS −12.6 kcal⋅mol−1) > [Cu-NHC1]-6JBR (DS −12.3 kcal⋅mol−1). In theory, this study suggests a potentiality of copper lighter tetrylenes and their derivatives against the infection of fungi Rhizoctonia solani and Magnaporthe oryzae, thus encouraging attempts for experimental developments.